2006
DOI: 10.2353/ajpath.2006.050766
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Type 1 Prion Protein in Variant Creutzfeldt-Jakob Disease

Abstract: Molecular typing of the abnormal form of the prion protein (PrP Sc) has come to be regarded as a powerful tool in the investigation of the prion diseases. All evidence thus far presented indicates a single PrP Sc molecular type in variant Creutzfeldt-Jakob disease (termed type 2B), presumably resulting from infection with a single strain of the agent (bovine spongiform encephalopathy). Here we show for the first time that the PrP Sc that accumulates in the brain in variant CreutzfeldtJakob disease also contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
2
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 20 publications
6
107
2
1
Order By: Relevance
“…We agree with Yull et al 35 and Polymenidou et al 34 that the detection of type 1 and 2 co-occurrence using a conventional typing method and antibodies recognizing both types may lack sufficient sensitivity. In this regard, we were able to increase the sensitivity of the type 1 and 2 co-occurrence signal up to the value of 10% (weak band of one type/total PrP Sc ) using a conventional gel electrophoresis system and up to Figure 8 Detection limit of PrP Sc types 1 and 2 co-occurrence by 3F4.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…We agree with Yull et al 35 and Polymenidou et al 34 that the detection of type 1 and 2 co-occurrence using a conventional typing method and antibodies recognizing both types may lack sufficient sensitivity. In this regard, we were able to increase the sensitivity of the type 1 and 2 co-occurrence signal up to the value of 10% (weak band of one type/total PrP Sc ) using a conventional gel electrophoresis system and up to Figure 8 Detection limit of PrP Sc types 1 and 2 co-occurrence by 3F4.…”
Section: Discussionsupporting
confidence: 78%
“…PrP Sc types co-occurrence in CJD S Notari et al that PrP Sc type 1 regularly coexist in CJD previously classified as type 2. 34, 35 We also detected a type 1-like band in all CJD type 2 subtypes but came up to a different conclusion concerning the origin and biological significance of this band. In a previous study, 30 where we originally applied a highresolution electrophoretic system, which better discriminates between distinct PrP isoforms, we showed that PK digestion of both PrP Sc types 1 and 2 produces additional fragments migrating slightly slower than the resistant core.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The 3F4 and 6H4 antibodies both detect epitopes present in denatured PrP C and PrP Sc . Their specificity for PrP res in Western blotting is dependent on the presence of the 3F4 and 6H4 epitopes in the protease-resistant core fragment of PrP res [11,12,26]. The 3F4 antibody (CE marked) has been consistently used for over 10 years in diagnostic testing for human prion disease by the majority of human prion disease surveillance and research centres worldwide [11,12,27,28].…”
Section: Primary Antibodiesmentioning
confidence: 99%